Evaluation and comparison of staining patterns of factor XIIIa (AC‐1A1), adipophilin and GATA3 in sebaceous neoplasia. (19th September 2017) - Tjarks, Brian J.; Pownell, Brandy R.; Evans, Claire; Thompson, Paul A.; Kerkvliet, Amy M.; Koch, Michael R. D.; Jassim, Ali D.
Abstract : Background: Reliable nuclear immunohistochemical stains for sebaceous neoplasms have not been readily available. Positive nuclear staining has been reported for GATA3 and factor XIIIa (AC‐1A1). We sought to determine the diagnostic utility of these nuclear stains by comparing their staining pattern to adipophilin, a consistently positive cytoplasmic stain. Methods: Cases with the diagnosis of sebaceous hyperplasia, sebaceous adenoma, sebaceous epithelioma/sebaceoma, sebaceous carcinoma, and nonsebaceous neoplasms (basal cell carcinoma and squamous cell carcinoma) were examined. Intensity and extent of staining of the basal cells and mature sebocytes were evaluated for each stain. Results: Factor XIIIa (AC‐1A1) was 87.3% sensitive and 95.1% specific for all sebaceous neoplasms sand showed high inter‐observer reliability. Adipophilin was 83.2% sensitive and 87.8% specific. GATA3 was the least sensitive (80.9%) and specific (75.6%) marker. When factor XIIIa was compared against composite staining of all three markers its staining was still uniquely significant ( P  = .0210). Conclusion: Factor XIIIa (AC‐1A1) is a sensitive and specific nuclear marker for sebaceous differentiation. Its diagnostic utility exceeds that of adipophilin. Factor XIIIa should be included in the expanding group of immunohistochemical and special stains which can be utilized to aid in the diagnosis of sebaceous neoplasms.